Avifaunal inventory of northern Entre Ríos, Argentina: noteworthy records and conservation prospects - Dardanelli, Sebastián (2019)
Biodiversity inventories remain fundamental tools for biodiversity conservation. Neotropical biota has poor faunal inventories. In Argentina, the avifauna of the province of Entre Ríos is still not well known. Here, we present the first exhaustive bird inventory of Northern Entre Ríos. We recorded 317 bird species. Three species were new for the province of Entre Ríos and eight were new for Northern Entre Ríos. We recorded 17 threatened species, 4 biome-restricted species and two restricted range species. The high bird diversity of Northern Entre Ríos contrasts with the lack of effective reserves to ensure the survival of endangered species. Creation of natural reserves in this area is urgent. These protected areas should have a management plan and stable park rangers assigned, to ensure the protection of the avian diversity of Northern Entre Ríos.